Same proof, different pudding: comparative views of New Zealand child psychiatrists, child psychologists and child psychotherapists regarding a proposed national child and adolescent research network. (October 2020) - Thabrew, Hiran; Moor, Stephanie; Eggleston, Matthew
Objectives: This study was undertaken to evaluate the views of New Zealand clinicians regarding a proposed national child and adolescent mental health research network. Methods: Child psychiatrists, child psychologists and child psychotherapists were invited to participate in an electronic survey describing their previous experience of research, current interest in research, barriers to undertaking research and interest in a national research network. Results: Responses were received from child psychiatrists ( N = 33), child psychologists ( N = 58) and child psychotherapists ( N = 8), many of whom were clinicians and few of whom were researchers. Although most clinicians were interested in participating in future research, areas of interest differed between clinical groups. Clinician barriers to research included lack of time, lack of confidence and lack of research skills. Researcher barriers included lack of funding, time and administrative support. All groups were supportive of the development of a national research network. Conclusions: Despite some different areas of interest, there appears to be sufficient combined support from New Zealand child psychiatrists, child psychologists and child psychotherapists to pursue the establishment of a national child and adolescent mental health research network.